1999
DOI: 10.1271/bbb.63.1203
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Evolution in the Protein-coding Region of Galectin cDNAs, Congerin I and Congerin II, from Skin Mucus of Conger Eel (Conger myriaster)

Abstract: Two cDNAs encoding galectins named congerins I and II from the skin mucus of conger eel (Conger myriaster) were isolated and sequenced. Comparison of the nucleotide sequences of congerins I and II showed that the sequence similarities of the 5' and 3' untranslated regions (86 and 88%, respectively) were much higher than those of the protein-coding region (73%). The numbers of nucleotide substitutions per site (KN) for the untranslated regions are smaller than the numbers of nucleotide substitutions per synonym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…S1B). In general, Con-P was expressed in almost all of the various tissues analyzed except for spleen; however, expression of Con I and Con II was restricted to the skin and upper digestive tract as reported previously (4,24). In some specimens, Con-P was the only congerin isotype expressed in the peritoneal cells and was also transcribed in encapsulated bodies in the abdominal cavity.…”
Section: Detection and Sequencing Of A Novel Galectin From The Abdomisupporting
confidence: 76%
See 2 more Smart Citations
“…S1B). In general, Con-P was expressed in almost all of the various tissues analyzed except for spleen; however, expression of Con I and Con II was restricted to the skin and upper digestive tract as reported previously (4,24). In some specimens, Con-P was the only congerin isotype expressed in the peritoneal cells and was also transcribed in encapsulated bodies in the abdominal cavity.…”
Section: Detection and Sequencing Of A Novel Galectin From The Abdomisupporting
confidence: 76%
“…The conger eel (Conger myriaster) contains two prototype galectins, congerins I and II (Con I and II), that are found in the skin mucus and frontier organs that delineate the body from the outer environment, such as the epidermal club cells of the skin, wall of the oral cavity, pharynx, esophagus, and gills (3,4). Con I and II are prototype galectins, composed of subunits containing 135 and 136 amino acids, respectively, and display 48% amino acid sequence identity (4 -6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of congerins I and II, they can recognize some marine bacteria such as Vibrio anguillarum [198]. Investigation of their localization in fish tissues suggested that they are expressed not only in skin but also in the upper digestive tract and gill filament [198,199]. Eel has an additional lectin, AJL-2, which has a highly conserved sequence of C-type lectins, but displays Ca2q-independent activity.…”
Section: Lectinsmentioning
confidence: 99%
“…In fish, conger eel and electric eel have the proto-type galectin homologous protein and/or gene (Paroutaud et al, 1987;Muramoto & Kamiya, 1992;Ogawa et al, 1999). Eel proto-type galectin was isolated from the electric organ of Electrophorus electricus and found to have a prophylactic and therapeutic action on the experimental autoimmune myasthenia gravis in rabbit.…”
Section: Introductionmentioning
confidence: 99%